Local community dependence on salt licks in North and Central Sarawak, Malaysia (Borneo) - Hidayah, Nurul Asna; YUS AMIRA, YUSAIMI; Samuel, Lihan; Poline, Bala; Mohd Azlan, Jayasilan (Malaysia Nature Society, 2024)
Local communities worldwide utilise natural salt licks for hunting or extracting salts. In Sarawak, salt licks are not protected by legislation, and limited documentation is available regarding the community dependence on such resources. This study investigates the dependence of indigenous Sarawak communities on natural salt licks. A quantitative questionnaire survey using snowball sampling approach was conducted, targeting 27 individuals from communities residing nearby nine salt licks in northern and central Sarawak. These communities included the Kenyah (18), Iban (four), Berawan (three), Kelabit (one) and others (one). The survey revealed that the salt licks were mainly utilised for hunting (92.6%) or to collect salt (7.4%). A majority of respondents (57.1%) reported catching one to two animals on each hunting trip near a salt lick. Sambar deer (38.5%) was recorded as the most commonly observed animal at these sites, followed by wild boar (24.6%) and muntjacs (15.4%). Other species include macaques (10.8%), langurs (7.7%) and mousedeers (3.1%). The study highlights the importance of salt licks and can be used to formulate the development of conservation strategies and management plans for these sites in Sarawak.